The Evaluation of Diagnostic Tests for Sexually Transmitted Infections - Max A Chernesky (Canadian Journal of Infectious Diseases and Medical Microbiology)
Diagnostic tests should receive method- and use-effectiveness evaluations. Method-effectiveness evaluations determine sensitivity, specificity and predictive values for new tests. Use-effectiveness evaluations determine how practical or convenient a new test will be in a specific setting and may not be performed in a formal way in North American laboratories. To perform a clinical method evaluation of diagnostic tests, a good relationship between laboratory and clinical personnel is essential. Studies are usually conducted separately on populations of men and women, and should include sampling from different prevalence groups. Test performance comparisons may be made on a single specimen type or on more than one specimen from the same patient, which allows for the expansion of a reference standard and includes the ability of a particular assay, performed on a specimen type to diagnose an infected individual. The following components of the evaluation should be standardized and carefully followed: specimen identification; collection; transportation; processing; quality control; reading; proficiency testing; confirmatory testing; discordant analysis -- sensitivity, specificity and predictive value calculations; and record keeping. Methods are available to determine whether sample results are true or false positives or negatives. Use-effectiveness evaluations might determine the stability or durability of supplies and equipment; the logistics of shipping, receiving and storing supplies; the clarity and completeness of test instructions; the time and effort required to process and read results; the subjectivity factors in interpretation and reporting; and the costs. These determinations are usually more apparent for commercial assays than for homemade tests.